Violence and trauma and the influence of Francis Bacon in the paintings of Robert Hodgins - Jansen van Vuuren, Nathan (My University, 2012)
In this research I critically examine features of violence and the related notion of trauma as articulated through visual-formal language in the figurative paintings of contemporary South African artist Robert Hodgins. The significant influence of Francis Bacon pertaining to these themes is considered in examining Hodgins’ presentation of the human body within extremes. Both artists’ paintings focus on the human figure and allude to violence and the experience of trauma in their iconography but I also examine their expressive handling of medium as critical to reading such artworks in terms of trauma. I examine recent trauma theory and its application to the visual arts to locate my discussion around Hodgins’ paintings as approaching trauma through certain affective dynamics. I then examine Hal Foster’s analysis of Andy Warhol’s Death in America images and how the concept of trauma and affect are seen to be significantly internal to such artworks. I subsequently consider how Hodgins’ paintings may be seen to address psychological trauma as an experience of an event that the subject cannot fully integrate into his/her experience. My primary aim is to investigate the strategies and approaches which Hodgins employs and how the works are realised as a transmittable language of sensation through the visual medium of paint and its subsequent affect. As such it is an enquiry into how Hodgins’ paintings can be seen to embody experience. In a final chapter I discuss my own concerns in the paintings submitted towards this degree in light of the above.
M.A. Faculty of Humanties, University of the Witwatersrand, 2011